2013
DOI: 10.1016/j.tourman.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of the hotel industry in Singapore

Abstract: Existing literature related to evaluating the efficiency of the hotel industry, generally, uses different types of radial Data Envelopment Analysis (DEA) to compare the relative efficiency of different hotels in a location. This research note has adopted a different approach by treating years as decision making units (DMUs). This will allow policymakers to evaluate the relative efficiency of a hotel industry as a whole over a specified time period so that the effects of the occurrence of events on the efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Barros and Santos (2006) propose that for improving efficiency an enhanced-incentive policy should be implemented, as well as to upgrade the quality of hotel management practices, adjust prices according to market demands, ensure better labour controls and adopt procedures for benchmarking. Ashrafi, Seowb, Lee, and Lee (2013) tried a different approach. They treated years as DMUs and in this way they evaluated efficiency of the hotel industry as a whole on sample hotels in Singapore.…”
Section: Data Envelopment Approach In the Hospitality Industrymentioning
confidence: 99%
“…Barros and Santos (2006) propose that for improving efficiency an enhanced-incentive policy should be implemented, as well as to upgrade the quality of hotel management practices, adjust prices according to market demands, ensure better labour controls and adopt procedures for benchmarking. Ashrafi, Seowb, Lee, and Lee (2013) tried a different approach. They treated years as DMUs and in this way they evaluated efficiency of the hotel industry as a whole on sample hotels in Singapore.…”
Section: Data Envelopment Approach In the Hospitality Industrymentioning
confidence: 99%
“…Quite often, they are expanded to multiple outputs and multiple inputs. Outputs are evaluated in the forms of room revenue, revenue per room, sales, gross letting, total revenue or tourism receipts (Anderson et al 1999; Anderson, Fok, and Scott 2000; Ashrafi et al 2013; Barros 2005a, 2005b; Barros and Dieke 2008; Barros and Santos 2006; Chen 2009; Hwang and Chang 2003; Morey and Dittman 1995; Peypoch 2007; Reynolds 2003), food and beverage revenue (Ashrafi et al 2013; Chiang, Tsai, and Wang 2004; Hwang and Chang 2003; Johns, Howcroft, and Drake 1997), occupancy rate (Ashrafi et al 2013; Chen 2009), operational cost (Barros 2004, 2006), customer satisfaction (Brown and Ragsdale 2002; Reynolds and Biel 2007), visitor numbers, visitor room nights (Johns, Howcroft, and Drake 1997), number of guests (Barros 2005a, 2005b; Chen 2009), and number of trips (Anderson, Lewis, and Parker 1999).…”
Section: An Overview Of Productivity Methodologiesmentioning
confidence: 99%
“…Inputs include labor (full-time equivalent [FTE]), costs of labor, hours worked, average wages, price of capital, price of materials, total costs (Reynolds 2003; Barros 2004, 2005a), ownership forms of hotels (Oliveira, Pedro, and Marques 2013b; Ortega and Chicón 2013; Perrigot, Cliquet, and Piot-Lepetit 2009), surface area in square meters, rooms and median price (Brown and Ragsdale 2002; Tsaur 2001; Wang, Hung, and Shang 2006), customer satisfaction (Assaf and Magnini 2012), hotel star-rating (Oliveira, Pedro, and Marques 2013a), natural resources (Hadad et al 2012), the role of information communication technologies (Li 2014; Sigala 2003), the number of schooling years of staff (Ortega and Chicón 2013), nights slept (Barros and Santos 2006), and the number of years in business (Assaf and Agbola 2011). Surprisingly, tourist numbers or number of guests were used in relation to both aspects of hospitality: as an input measure (Ashrafi et al 2013) and an output measure, as seen in many of the studies mentioned previously.…”
Section: An Overview Of Productivity Methodologiesmentioning
confidence: 99%
“…However, these assumptions do not conform with reality. Therefore, some scholars applied the nonradial DEA model proposed by Tone (2001) to study hotel efficiency (Ashrafi et al, 2013; Cheng et al, 2010; Chiu et al, 2012; Cruz, 2017; Sun and Lu, 2005; Untong, 2013; Wu et al, 2011; Yang and Lu, 2006). For example, Chiu et al (2012) compared the efficiency of 58 international tourism hotels in Taiwan with radial and nonradial models and found that inefficient hotels calculated with the radial model had become inefficient hotels under the nonradial model, and efficiencies measured by the nonradial model were always lower than those with the radial model.…”
Section: Literature Reviewmentioning
confidence: 99%